Kidney Autotransplantation and Orthotopic Kidney Transplantation: Two Different Approaches for Complex Cases - Alberto Artiles Medina; Victoria Gómez Dos Santos; Víctor Díez Nicolás; Vital Hevia Palacios; Mercedes Ruiz Hernández; Inés Laso García; Marina Mata Alcaraz; Cristina Galeano Álvarez; Miguel Ángel Jiménez Cidre; Fernando Arias Fúnez; Milagros Fernández Lucas; Francisco Javier Burgos Revilla (Advances in Urology)
Introduction. Transplantation surgery teams often have to face complex cases. In certain circumstances, such as occlusion of the iliac vessels or prior pelvic surgery, heterotopic kidney transplantation may not be feasible and orthotopic kidney transplantation (OKT) could be a good alternative. Kidney autotransplantation (KAT) has been described as a potential treatment for complex renovascular, ureteral, or neoplastic conditions. There are scarce data regarding the complications and outcomes of these procedures; therefore, we present our experience. Materials and Methods. We retrospectively analysed the medical records of both 21 patients who had received OKT and 19 patients who underwent KAT between 1993 and 2020. We collected demographic features and data regarding surgical technique, complications, and graft outcomes. Kidney graft survival was calculated using Kaplan–Meier survival analysis. Results. Regarding OKT, in 15 (71.43%) cases, it was the first kidney transplantation. The most common indication was the unsuitable iliac region due to vascular abnormalities (57.14%). The early postoperative complication rate was high (66.67%), with 23.81% of Clavien grade 3b complications. During the follow-up period (mean 5.76 -SD 6.15- years), we detected 9 (42.85%) graft losses. At 1 year, the survival rate was 84.9%. Concerning KAT, the most frequent indication was ureteral pathology (52.63%), followed by vascular lesions (42.11%). The overall early complication rate was 42.11%. During the follow-up period (mean of 4.47 years), 4 (15.79%) graft losses were reported. Conclusions. Although OKT and KAT have high complication rates, these techniques can be considered as two valuable approaches for complex cases, in the absence of other therapeutic options.